A Embrapa e a universidade - Quirino, Tarcízio Rego; Castro, Antônio Maria Gomes de (Cadernos de Ciência & Tecnologia, 1992)
Relatam-se as relações entre a Embrapa e as universidades no tocante a formas de cooperação, formação de mão-de-obra, intercâmbio de recursos humanos, apoio financeiro e uso de instalações. Em seguida, apresenta-se a nova perspectiva da Empresa rumo ao século XXI e discorre-se sobre a nova demanda por profissionais da agricultura sustentada. Embrapa and the University Abstract The relationships between Embrapa and the University as to cooperation forms, undergraduation and graduation, human resource interchange, research funding, and facilities utilization are reported. The new perspective of Embrapa for the XXI century and the new demand for sustainable agricultural-oriented professionals are discussed.